Noninvasive Imaging of Quantitative Cerebral Blood Flow Changes during 100% Oxygen Inhalation Using Arterial Spin-Labeling MR Imaging - Zaharchuk, G.; Martin, A.J.; Dillon, W.P. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Tracer studies have demonstrated that 100% oxygen inhalation causes a small cerebral blood flow (CBF) decrease. This study was performed to determine whether arterial spin-labeling (ASL), a noninvasive MR imaging technique, could image these changes with clinically reasonable imaging durations.Materials and METHODS: Continuous ASL imaging was performed in 7 healthy subjects before, during, and after 100% oxygen inhalation. ASL difference signal intensity (ΔM, control − label), CBF, and CBF percentage change were measured. A test-retest paradigm was used to calculate the variability of the initial and final room air CBF measurements.RESULTS: During oxygen inhalation, ΔM decreased significantly in all regions (eg, global ΔM decreased by 23 ± 11%, P < .01, all values mean ± SD). Accounting for the reduced T1 of hyperoxygenated blood, we found a smaller CBF decrease, which did not reach significance in any of the regions. Global CBF dropped from 50 ± 10 mL per 100 g/minute to 47 ± 10 mL per 100 g/minute following 100% oxygen inhalation, a decrease of 5 ± 14% (P > .17). The root-mean-square variability of the initial and final room air CBF measurements was 7–8 mL per 100 g/minute.CONCLUSIONS: The ΔM signal intensity decreased significantly with oxygen inhalation; however, after accounting for changes in blood T1 with oxygen, CBF decreases were small. Such measurements support the use of hyperoxia as an MR imaging contrast agent and may be helpful to interpret hyperoxia-based stroke trials.